Participative Leadership by American and Chinese Managers in China: The Role of Relationships* - Chen, Yi Feng; Tjosvold, Dean (Journal of Management Studies, 2006)
abstract Developing participative leadership may be particularly challenging when managers are working cross‐culturally and in China. One hundred and sixty‐three Chinese employees from various industries in mainland China were surveyed about their relationships and the effectiveness of their participation with American and Chinese managers. Results, including structural equation analyses, support the hypotheses that cooperative, but not competitive or independent, goals helped Chinese employees and their foreign and Chinese managers strengthen their quality relationships as measured by supervisor–subordinate guanxi and leader–membership exchange; quality relationships in turn enhanced effective participative leadership as measured by the opportunity for joint decision‐making and the open‐minded discussion of opposing views (constructive controversy). Results suggest that cooperative goals and the Chinese value of guanxi may be important for overcoming obstacles and developing participative leadership within and across cultural boundaries.